Effect of Skills, Capabilities, Education and Training on Accounting Information System User Satisfaction - Holiawati, Holiawati (EAJ (Economic and Accounting Journal), 2019)
This study aims to examine the effect of skills, abilities, education and training on the satisfaction of users of accounting information. The research method uses quantitative methods. The sample in this study were UNPAM students who worked as accounting and had received education and accounting information system training and training. The results of this study are the influence of skills on the satisfaction of users of accounting information, there is an influence on the ability of users of accounting information satisfaction and there is no influence of education and training on the satisfaction of users of accounting information.